Performance of hybri d fiber reinforced geopolymer composites: scientometric and conventional review - Al-Baldawi, Maryam Firas; Abdul Aziz, Farah Nora Aznieta; Noor Abbas, Al Ghazali; Mohd Nasir, Noor Azline; Mohamed Sutan, Norsuzailina (Universiti Putra Malaysia Press, 2024)
Hybrid fibers are an interesting addition to reinforce geopolymer-based composites due to their advantages over single-fiber reinforcement. The performance of hybrid fibers is dependent on the fibers' composition, type, properties, length, and volume fraction. Therefore, this review discusses the state-of-the-art hybrid fiber-reinforced geopolymer composites (HFRGC) through two approaches: scientometric analysis and conventional review of HFRGC based on data extracted from Scopus from 2013 until 2023. The scientometric analysis was carried out by adopting VOS Viewer software and focuses on the annual publication of documents, top publication sources, co-occurrence keywords, researchers, top-cited papers, and countries. In contrast, the desk study refers to experimental data on the fresh properties and compressive, tensile, and flexural properties of HFRGC. This review output aids researchers in networking, promoting cooperative research, exchanging ideas, and creating joint ventures among researchers of HFRGC worldwide. The performance of HFRGC obtained from the desk study showed the potential of HFRGC as an option for a greener composite that will benefit the construction industry.